Strategi Dinas Kesehatan Kabupaten Karawang Dalam Meningkatkan Mutu Pelayanan Vaksinasi Covid-19 - Rahdian, Farhan; Muslihat, Asep (Jurnal Ilmiah Wahana Pendidikan, 2023)
At the end of 2020, Indonesia, including Karawang Regency, is being tested in the form of health cases that need to be worried about. This is a concern for all the people of Karawang Regency due to the spread of the virus or COVID-19 disease. Several efforts have been made by the government to minimize the transmission of Covid-19, namely by administering the Covid-19 vaccine. The purpose of this study is to find out what strategies need to be implemented in improving the quality of Covid-19 vaccination services. The qualitative method used in this research is a descriptive approach. The results of this study are in the form of a strategy that need to be implemented in improving the quality of Covid-19 vaccination services such as accessibility, information and communication, public service innovation and medical staff training. Furthermore, the benefit of this research is that it can be a reference in improving the quality of Covid-19 vaccine services